The Pomegranate: Effects on Bacteria and Viruses That Influence Human Health. (20th May 2013) - Howell, Amy B.; D'Souza, Doris H.
Abstract : Pomegranates have been known for hundreds of years for their multiple health benefits, including antimicrobial activity. The recent surge in multidrug-resistant bacteria and the possibility of widespread global virus pandemics necessitate the need for additional preventative and therapeutic options to conventional drugs. Research indicates that pomegranates and their extracts may serve as natural alternatives due to their potency against a wide range of bacterial and viral pathogens. Nearly every part of the pomegranate plant has been tested for antimicrobial activities, including the fruit juice, peel, arils, flowers, and bark. Many studies have utilized pomegranate peel with success. There are various phytochemical compounds in pomegranate that have demonstrated antimicrobial activity, but most of the studies have found that ellagic acid and larger hydrolyzable tannins, such as punicalagin, have the highest activities. In some cases the combination of the pomegranate constituents offers the most benefit. The positive clinical results on pomegranate and suppression of oral bacteria are intriguing and worthy of further study. Much of the evidence for pomegranates' antibacterial and antiviral activities against foodborne pathogens and other infectious disease organisms comes from in vitro cell-based assays, necessitating further confirmation of in vivo efficacy through human clinical trials.